PENERAPAN PENDIDIKAN KARAKTER KEJUJURAN DAN TANGGUNGJAWAB MELALUI PEMBELAJARAN AGAMA DI SD NEGERI 41 KOTA BENGKULU - Atik Kurniawati; Nuzi Oktavia; Selvi Yani; Depi Helena; Betti Dian Wahyuni (Journal of Primary Education (JPE), 2024)
The implementation of character education at SD Negeri 41 Bengkulu City, particularly in teaching the values of honesty and responsibility through religious studies, has had a positive impact on students' character development. Despite challenges, such as limited learning time and lack of variety in teaching methods, students perceive significant benefits from this character education. Students expressed that character education does not only teach theory but also internalizes the values in their daily lives. However, the main challenge faced is the limited time allocated for religious studies, which hinders more in-depth teaching of the values of honesty and responsibility. In addition, the diverse teaching methods applied by teachers, such as lectures and discussions, are sometimes not interesting enough for students. The limited learning media used is also an inhibiting factor that affects students' interest in the subject matter. The evaluation conducted does not yet reflect a thorough understanding of student character, as the main focus is more on academic grades. The diversity of students' backgrounds and the lack of parental support are also inhibiting factors in the optimal implementation of character education. Therefore, to overcome these challenges, a more adequate evaluation of time allocation is needed, as well as the use of more varied teaching methods and involving support from parents. Despite the obstacles, the implementation of character education that emphasizes the values of honesty and responsibility is expected to continue to grow and have a positive influence on student character in the future.